Genome-wide association study of monoclonal gammopathy of unknown significance (MGUS): comparison with multiple myeloma - Thomsen, Hauke; Chattopadhyay, Subhayan; Weinhold, Niels; Vodicka, Pavel; Vodickova, Ludmila; Hoffmann, Per; Nöthen, Markus M.; Jöckel, Karl-Heinz; Langer, Christian; Hajek, Roman; Hallmans, Göran; Pettersson-Kymmer, Ulrika; et al. (Leukemia, 2019)
Letter